MONO COMPONENT ADDITIONAL FOOD IN CHILDREN WITH CYSTIC FIBROSIS - E.M. Shadrina; S.A. Boykov; N.S. Shatokhina (Вопросы современной педиатрии, 2010)
Authors analyze an experience of nutrition with mono component additional food «Gerber» in 15 infants with cystic fibrosis. They estimated a safety of additional food and its effectiveness via proper individual nutrition list and laboratory data (changes in faeces analysis and state of intestinal biocoenosis).Key words: children, cystic fibrosis, additional food.(Voprosy sovremennoi pediatrii — Current Pediatrics. 2010;9(2):99-102)